Migrating Applications to the Cloud with Azure : Re-architect and rebuild your applications using cloud-native technologies /: Re-architect and rebuild your applications using cloud-native technologies. (2019) - Zaal, Sjoukje; Malik, Amit; Rossel, Sander; Marston, Jason; Wali, Mohamed; Demiliani, Stefano
No abstract available